2016
DOI: 10.1038/srep38453
|View full text |Cite
|
Sign up to set email alerts
|

Totally embedded hybrid thin films of carbon nanotubes and silver nanowires as flat homogenous flexible transparent conductors

Abstract: There is a great need for viable alternatives to today’s transparent conductive film using largely indium tin oxide. We report the fabrication of a new type of flexible transparent conductive film using silver nanowires (AgNW) and single-walled carbon nanotube (SWCNT) networks which are fully embedded in a UV curable resin substrate. The hybrid SWCNTs-AgNWs film is relatively flat so that the RMS roughness of the top surface of the film is 3 nm. Addition of SWCNTs networks make the film resistance uniform; wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 60 publications
(69 reference statements)
2
21
0
Order By: Relevance
“… 16 Pillai et al reported a conductive hybrid network consisted of silver nanowires (Ag NWs) and SWCNT, which has been demonstrated potential in high energy density flexible-solid-state supercapacitor. 17 Dong et al fabricated the Ag/CNTs networks for a highly conductive film. 18 Li et al theoretically investigated the atomic and electronic structures of silver-filled SWCNTs by using first-principles calculations.…”
Section: Introductionmentioning
confidence: 99%
“… 16 Pillai et al reported a conductive hybrid network consisted of silver nanowires (Ag NWs) and SWCNT, which has been demonstrated potential in high energy density flexible-solid-state supercapacitor. 17 Dong et al fabricated the Ag/CNTs networks for a highly conductive film. 18 Li et al theoretically investigated the atomic and electronic structures of silver-filled SWCNTs by using first-principles calculations.…”
Section: Introductionmentioning
confidence: 99%
“…It was supposed that top layers of rGO and CNTs could protect the AgNWs against corrosion and oxidation due to the variation of temperature and humidity. [16][17][18][19] The durability of the flexibility of the coatings according to the number of folding cycles was investigated by measuring (R − R 0 )/R 0 , as shown in Figure 3b. The experimental results showed that not only the material combination but also the layer stacking sequence affected the performance of the flexible conductive electrode.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, in the case of the rGO/CNT/AgNW coating, the CNT layer might keep the AgNWs attached to the substrate and rGO might prevent the CNT layer from deforming with a severe strain. [16][17][18][19] Next, the schematic designs of the wear mechanism of the contact sliding test can be described as shown in Figure 4d(1) and (2). Figure 4d(1) shows that the AgNW coating is easily removed by the tip-sliding motion.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the high cost and the scarcity of indium supply, has been the motivation for many researchers to find alternative solutions that are sustainable. [4,5] This includes metal microfiber, [6] nanowires, [7,8] polymers, [9] carbon nanotubes, [10,11] and graphene. [12,13] Among them, graphene has attracted more attention because of its high transparency, excellent electron mobility, good chemical, mechanical and thermal stability.…”
mentioning
confidence: 99%